Patterns of help-seeking behavior among people with mental illness in Ethiopia: a systematic review and meta-analysis - Asnakew, Sintayehu; Haile, Kalkidan; Kassa, Bekalu Getnet; Ayehu, Gashaw Wale; Beyene, Getnet Mihretie; Feleke, Dejen Getaneh; Endalew, Desalegn Gizachew; Legas, Getasew; Munie, Birhanu Mengist; Tedila, Assasahegn; Shiferaw, Kirubel; Belete, Amsalu; et al. (Frontiers in Psychiatry, 2024)
Background: Even though evidence-based effective treatments are available, significant numbers of people living with mental illness didn’t seek help from the modern treatment. Therefore, this review was intended to investigate the pooled pattern of help-seeking behavior of individuals with mental illness in Ethiopia. Methods: All the available primary studies were searched through Google scholar, HINARI, and, PubMed databases from June 22- December 20 /2023 giving 912 articles. Sixteen articles were included in the final review and data were extracted on an Excel spreadsheet and exported to Stata version 17 for analysis. The search terms used were: “Pattern of help seeking behavior’’ OR “Pattern of Treatment Seeking Behavior” OR “Health Care Seeking Behavior” OR “Help Seeking Intention” OR “Help-Seeking Preferences” OR “perceived need”, OR “Pathways to psychiatric care” AND “Common Mental Disorders” OR “Mental Illness” OR “Mental Health Problems “OR “Depression” AND “Predictors” OR “Determinate Factors” OR “Associated Factors” AND “Ethiopia”. Quality was critically appraised by the modified Newcastle-Ottawa quality assessment tool scale adapted for observational studies. Disagreements between the two authors were resolved by the involvement of a third author. Effect sizes were pooled using the random-effects model and the presence of publication bias was detected from asymmetry of funnel plot and statistically significant Egger's test (p<0.05). Results: The pooled pattern of good help-seeking behavior of people living with mental illness to the modern treatment was 42.21 %( 95%CI: 29.29, 55.12, I2=99.37%, P=0.00). Secondary education and above (AOR=5.47, 95%CI: 2.33, 12.86), thinking mental illness need treatment (AOR=2.76, 95%CI: 2.02, 3.78), having strong social support (AOR=2.00, 95%CI: 1.64, 2.44), family history of mental illness(AOR=2.68, 95%CI: 1.38, 3.97), know the availability of treatment (AOR=2.92,95%CI: 1.56, 5.46), having previous good help-seeking behavior (AOR=3.28,95%CI: 1.63, 6.60),comorbid disorder (AOR=4.25,95%CI: 1.69, 10.66), did not use alcohol(AOR=3.29, 95%CI: 1.73, 6.27), and having perceived severity of mental illness (AOR=2.54, 95%CI: 1.490,4.33) were significantly associated with good pattern of help-seeking behavior. Conclusions: The majority of people with mental illness had poor pattern of help-seeking behavior. Therefore, it should be encouraged to mobilize the community via regular public awareness about mental illness and the availability of evidence and effective treatment.